On the Role of Theta-Driven Syllabic Parsing in Decoding Speech: Intelligibility of Speech with a Manipulated Modulation Spectrum - Ghitza, Oded (Frontiers in Psychology, 2012)
Recent hypotheses on the potential role of neuronal oscillations in speech perception propose that speech is processed on multi-scale temporal analysis windows formed by a cascade of neuronal oscillators locked to the input pseudo-rhythm. In particular, Ghitza (2011) proposed that the oscillators are in the theta, beta and gamma frequency bands with the theta oscillator the master, tracking the input syllabic rhythm and setting a time-varying, hierarchical window structure synchronized with the input. In the study described here the hypothesized role of theta was examined by measuring the intelligibility of speech with a manipulated modulation spectrum. Each critical-band signal was manipulated by controlling the degree of temporal-envelope flatness. Intelligibility of speech with critical-band envelopes that are flat is poor; inserting extra information, restricted to the input syllabic rhythm, markedly improves intelligibility. It is concluded that flattening the critical-band envelopes prevents the theta oscillator from tracking the input rhythm, hence the disruption of the hierarchical window structure that controls the decoding process. Reinstating the input-rhythm information revives the tracking capability, hence restoring the synchronization between the window structure and the input, resulting in the extraction of additional information from the flat modulation spectrum.